Not all hairy cells are the same: a rare case of splenic B-cell lymphoma/leukaemia with prominent nucleoli - Jaine, Nagarjun Sai; Chandrasekhar, Beena; Mehra, Kailash Singh; Maurya, Sunny Kumar (International Journal of Research in Medical Sciences, 2025)
A peripheral blood sample from an 81-year-old male was received at our stand-alone reference laboratory for evaluation in the setting of fever, progressive fatigue over 3 months, and early satiety. On clinical examination, he had significant pallor and a firm, non-tender splenomegaly extending 6 cm below the costal margin. There was no hepatomegaly or lymphadenopathy.